Play dough or balloon blowing? A clinical trial comparing creative interventions for reducing preoperative anxiety in children aged 4–8 years - Razie Vakili; Reza Feizi; Yahya Salimi; Mobin Mottahedi; Parisa Rizevandi (BMC Pediatrics)
Abstract Background Preoperative anxiety is a significant concern for pediatric patients undergoing surgery, often leading to adverse physiological, emotional, and postoperative outcomes. Traditional pharmacological approaches, while effective, are associated with side effects, underscoring the need for age-appropriate non-pharmacological interventions. This study aimed to compare the effectiveness of play dough (PD) activities and balloon blowing (BB) in reducing preoperative anxiety in children. Methods This randomized controlled trial included 90 children aged 4–8 years, a developmental stage characterized by responsiveness to play-based interventions, scheduled for elective surgeries at Besat Hospital, Hamedan, Iran, between November 2023 and January 2025. Participants were randomized into three groups: PD, BB, and Control (standard care with midazolam). Anxiety levels were assessed at baseline (T0), immediately before entering the operating room (T1), and during anesthesia induction (T2) using the Modified Yale Preoperative Anxiety Scale (m-YPAS) and the Visual Analog Scale for Anxiety (VAS-A). Each intervention was administered for 15 min under direct supervision by a trained researcher. Statistical analysis included ANOVA for continuous variables and chi-square tests for categorical variables. Post hoc comparisons were performed using Tukey’s method. Results At T1 and T2, children in the PD and BB groups exhibited significantly lower anxiety levels compared to the Control group (P < 0.001). For m-YPAS scores at T1, the PD group mean 36.05 ± 4.28, and the BB group 35.15 ± 2.94, compared to 54.55 ± 4.05 in the Control group. Similar trends were noted at T2. VAS-A analysis further supported these findings, with the PD and BB groups showing higher proportions of mild anxiety compared to the Control group. No significant differences were detected between the PD and BB groups, indicating that both interventions were comparably effective. Conclusions PD and BB are effective non-pharmacological interventions for reducing preoperative anxiety in children. These cost-effective, engaging techniques offer safe alternatives to pharmacological treatments and promote emotional well-being. The findings support integrating age-appropriate, creative, play-based strategies into pediatric surgical care, emphasizing their potential to enhance the preoperative experience and improve outcomes. Future research should investigate long-term impacts, applicability across diverse populations, and comparative efficacy in various clinical settings. Trial registration Registered in the Iranian registry of clinical trials ( https://irct.behdasht.gov.ir ) in 19/11/2023 with the following code: IRCT20230514058183N1.